The relationship of stress and locis of control to academic procrastination in Ormawa student faculty of health Universitas Dian Nuswantoro - Muthoharoh, Nor Amalia; Mubarokah, Kismi; Aprianti, Aprianti; Amalia, Rika Juniar; Faddhlurrohman, Naufal Rizky (Institute of Computer Science (IOCS), 2024)
Academic procrastination is an activity of procrastinating work that students do when they get their main assignment, namely studying. This research was conducted with the aim of finding out whether there is an influence and relationship related to stress and local control on students who take part in student organization activities at the Faculty of Health, Dian Nuswantoro University through academic achievement index scores and questionnaires, especially students who are in the core organizational structure. This research will be carried out at 6 student organizations at the Faculty of Health, Dian Nuswantoro University in October 2023 – January 2024 (Suhandianto and Pratitis Nindia, 2020). Using survey methods with a quantitative correlational approach.(Siska Martiana et al., 2022)The results of the multiple regression analysis together show that there is an influence between the independent variables stress (X1) and Locus of Control (X2) on the dependent variable academic procrastination (Y) of 0.093, which means that there is an influence between the two independent variables on the dependent variable of 09.3 % and the remaining 90.7% is influenced by other variables not studied at this time. The results of the second hypothesis research test, namely the independent variables Stress (X1) and Locus of control (X2), which were tested simultaneously, have an influence on the Academic Procrastination variable (Y) which can be seen from the T and F tests. Where are the results of the T and F tests? The comparison value is obtained as Fcount equal to 2.971 < Ftable 3.156, then together with the stress variable (X1) we get a value of tcount 2,345 > Ttable 1.672 and the variable locus of control (X2) obtained a value of tcount 0,171 < ttable 1,672. In conclusion, there is a very significant influence between stress and student academic procrastination and there is an insignificant influence between locus of control and academic procrastination. This means that if the locus of control results are low, students are classified as having an internal locus of control which has little influence on the occurrence of academic procrastination.